A touching advantage: cross-modal stop-signals improve reactive response inhibition - Maximilian A. Friehs; Philipp Schmalbrock; Simon Merz; Martin Dechant; Gesa Hartwigsen; Christian Frings (Experimental Brain Research, 2024)
The ability to inhibit an already initiated response is crucial for navigating the environment. However, it is unclear which characteristics make stop-signals more likely to be processed efficiently. In three consecutive studies, we demonstrate that stop-signal modality and location are key factors that influence reactive response inhibition. Study 1 shows that tactile stop-signals lead to better performance compared to visual stop-signals in an otherwise visual choice-reaction task. Results of Study 2 reveal that the location of the stop-signal matters. Specifically, if a visual stop-signal is presented at a different location compared to the visual go-signal, then stopping performance is enhanced. Extending these results, study 3 suggests that tactile stop-signals and location-distinct visual stop-signals retain their performance enhancing effect when visual distractors are presented at the location of the go-signal. In sum, these results confirm that stop-signal modality and location influence reactive response inhibition, even in the face of concurrent distractors. Future research may extend and generalize these findings to other cross-modal setups.

The influence of tDCS on perceived bouncing/streaming - Maximilian A. Friehs; Marlena J. Stegemann; Simon Merz; Christoph Geißler; Hauke S. Meyerhoff; Christian Frings (Experimental Brain Research, 2023)
Processing ambiguous situations is a constant challenge in everyday life and sensory input from different modalities needs to be integrated to form a coherent mental representation on the environment. The bouncing/streaming illusion can be studied to provide insights into the ambiguous perception and processing of multi-modal environments. In short, the likelihood of reporting bouncing rather than streaming impressions increases when a sound coincides with the moment of overlap between two moving disks. Neuroimaging studies revealed that the right posterior parietal cortex is crucial in cross-modal integration and is active during the bouncing/streaming illusion. Consequently, in the present study, we used transcranial direct current stimulation to stimulate this brain area. In the active stimulation conditions, a 9 cm 2 electrode was positioned over the P4-EEG position and the 35 cm 2 reference positioned over the left upper arm. The stimulation lasted 15 min. Each participant did the bouncing/streaming task three times: before, during and after anodal or sham stimulation. In a sample of N = 60 healthy, young adults, we found no influence of anodal tDCS. Bayesian analysis showed strong evidence against tDCS effects. There are two possible explanations for the finding that anodal tDCS over perceptual areas did not modulate multimodal integration. First, upregulation of multimodal integration is not possible using tDCS over the PPC as the integration process already functions at maximum capacity. Second, prefrontal decision-making areas may have overruled any modulated input from the PPC as it may not have matched their decision-making criterion and compensated for the modulation.